Cybersecurity in the age of internet of things: A review of challenges and solutions - Anyanwu, David (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2024)
The Internet of Things (IoT) represents a paradigm shift in the way we interact with technology and the world around us. The exponential growth of IoT devices has undoubtedly brought about numerous benefits, but it has also ushered in a wave of security risks and threats, posing threats to the integrity and security of this interconnected ecosystem. This surge in connectivity has also given rise to numerous cybersecurity challenges, posed by the inherent vulnerabilities in these devices. The integration of Artificial Intelligence (AI) has emerged as a pivotal force in fortifying cybersecurity measures. The security-by-design approach is crucial in addressing the cybersecurity challenges associated with the era of the Internet of Things. In addition, educating both end-users and industry stakeholders plays a crucial role in ensuring the integrity of interconnected systems. In this review, we discuss the current state of the art in the field of cybersecurity, focusing on the importance of a comprehensive and collaborative approach, encompassing technological advancements, regulatory measures, and user education, to ensure a resilient and trustworthy interconnected future.